ANALISIS NILAI KONSERVASI TINGGI ASPEK PENGENDALI EROSI DAN SEDIMENTASI (HCV 4.2) DI DAS CILIWUNG HULU - Nur Aida; Latief Mahir Rachman; Dwi Putro Tejo Baskoro (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Land use changes from forest to non forest on a large scale causing environmental damage and decrease the hydrologycal function of a watershed. The problem of forest change can be reduced by identifying, assessing and mapping of high coservation value areas based on requirements that led an area to be important outside the protected areas. This study was conducted at Ciliwung Upper Watershed. The aim of the research were identify the high conservation value areas base on environmental services aspect with erosion and sedimentation control (HCV 4.2), and b) analyze the consistency of HCV 4.2 to land capability class and Goverment Rule No 26 year 2008. The RUSLE equation to identify the area of HCV 4.2 is modified in HCV Toolkit that ignore the land management and conservation practice aspect. Land capability is classified base on Klingibel and Montgomary, but there are just 4 criteria which is used in this research (erosion, slope, depth of solum, and drainage). The result showed that 90% of total area of research was identified as area of HCV 4.2. There are 7 class of land capability (class I, II, III, IV, VI, VII and VIII) where the class IV and VIII are dominant in the area. From consistency analysis, it is known that 75% of area of HCV 4.2 is inconsistent with land capability class and Goverment Rule No 26 year 2008.